2010
DOI: 10.1080/10790268.2010.11689701
|View full text |Cite
|
Sign up to set email alerts
|

Fever During Rehabilitation in Patients With Traumatic Spinal Cord Injury: Analysis of 392 Cases From a National Rehabilitation Hospital in Turkey

Abstract: Objective: To determine the incidence and etiology of fever and the risk factors related to fever in adults with spinal cord injury (SCI) at the rehabilitation stage. Design/Subjects: A retrospective examination of records of 392 consecutive adult patients with traumatic SCI who received inpatient rehabilitation program. Setting: A national rehabilitation center in Turkey. Outcome Measures: Incidence and etiology of fever, period of hospitalization (days). Results: A total of 187 patients (47.7%) had fever at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…24 In another study from Turkey, 25 it was reported that the most common cause of SCI were falls (42.6%) and motor vehicle crash (38.5%), similarly as in the current study (35.0 and 34.2%, respectively). In addition, we found that the frequency of SCI due to falls was significantly higher in the painful group.…”
Section: Discussionsupporting
confidence: 84%
“…24 In another study from Turkey, 25 it was reported that the most common cause of SCI were falls (42.6%) and motor vehicle crash (38.5%), similarly as in the current study (35.0 and 34.2%, respectively). In addition, we found that the frequency of SCI due to falls was significantly higher in the painful group.…”
Section: Discussionsupporting
confidence: 84%
“…They are also well below fever thresholds of 99.5°F and 99.9°F as previously reported in SCI literature. 5,18 Most notably, they were also below 98.6°F, which is the "normal" core temperature of a healthy resting adult human. While this could have been a result of averaging 3 temperatures of the day of DI or due to administration of antipyretic medication as standard of care, it was a statistically significant rise from baseline temperature before DI (BT1) in both TP and PP groups (p = .0009 and .0216, respectively), so it was a true increase from baseline T au.…”
Section: Temperaturesmentioning
confidence: 98%
“…5,17,18 During acute hospitalization post SCI, 73% to 81% of fevers have been reported to be of infectious etiology, with urinary tract and respiratory infections being most common. 5,17,19,20 Furthermore, in a study of 88 SCI persons, temperatures greater than 101.5°F were more likely (but not always) to be of an infectious rather than noninfectious etiology.…”
Section: Does the Cdc Definition Of Fever Accurately Predict Inflammamentioning
confidence: 99%
See 2 more Smart Citations